2012
DOI: 10.1186/1746-6148-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Experimental H-type and L-type bovine spongiform encephalopathy in cattle: observation of two clinical syndromes and diagnostic challenges

Abstract: BackgroundThe majority of atypical bovine spongiform encephalopathy (BSE) cases so far identified worldwide have been detected by active surveillance. Consequently the volume and quality of material available for detailed characterisation is very limiting. Here we report on a small transmission study of both atypical forms, H- and L-type BSE, in cattle to provide tissue for test evaluation and research, and to generate clinical, molecular and pathological data in a standardised way to enable more robust compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
112
4
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(157 citation statements)
references
References 47 publications
(92 reference statements)
28
112
4
13
Order By: Relevance
“…This country imports meat and bone meal for feeding dairy cattle. Konold et al (2012) demonstrated that cattle exposed to meal containing the brain stem of animals infected with BSE develop the disease. Bovines from Turkey have a high frequency of the heterozygous 23-bp genotype and the 12-bp insertion genotype (Un et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This country imports meat and bone meal for feeding dairy cattle. Konold et al (2012) demonstrated that cattle exposed to meal containing the brain stem of animals infected with BSE develop the disease. Bovines from Turkey have a high frequency of the heterozygous 23-bp genotype and the 12-bp insertion genotype (Un et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The development of classic BSE may be associated with the incorporation of meat and bone meal containing PrP Sc into the bovine diet (Konold et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When discriminating the different forms of BSE, immunohistochemistry (IHC) in brain has been reported to allow discrimination of distinguishable immunolabelling patterns for C-BSE, L-BSE and H-BSE, especially when focusing on rostral areas of the brain, and cerebellum (Konold et al, 2012). Western blotting (WB) allows prompt identification of H-BSE cases according to the molecular mass of the unglycosylated PrP fraction and the detection of the protein by antibodies binding to N-terminal epitopes (e.g.…”
Section: Detection Of Infectionmentioning
confidence: 99%
“…Intracerebral challenge studies with both Atypical BSE forms were also performed by Konold et al (2012), in which PrP Sc deposition was identified in muscle spindles and in the trigeminal ganglion following a limited study of potential peripheral distribution. This study is described in more detail in Section 2.2.…”
Section: Information Available From Published Literaturementioning
confidence: 99%
“…Only one strain, classical BSE, was responsible for the BSE epidemic and the associated epidemic of vCJD 8 . The atypical H-type and L-type strains typically occur in cattle over eight years of age, and appear to arise spontaneously 9,10 .…”
Section: The Infectious Agentmentioning
confidence: 99%